APPLICATION OF BRACHYTHERAPY IN CHEMORADIATION OF SECONDARY VAGINAL CANCER USING DIFFERENT SOURCES OF RADIATION - Ivankova, V.S.; Baranovska, L.M.; Matviyevska, L.V.; Khrulenko, T.V. (World of Medicine and Biology, 2019)
Comprehensive conservative treatment was carried out for 93 patients with secondary vaginal cancer (SVC). Patients were divided into 3 groups depending on the source (192Ir, 60Co) and mode of brachytherapy (BT). There were two study groups being performed high-energy (HDR) BT with 192Ir source in different modes and the comparison group, being performed HDR BT with 60C sources. The treatment was carried out against the background of chemosensitizing agents. It was found that the positive response of the tumor after the course of chemo-radiation therapy was increased by 11.5% and 9.7% compared to the comparison group in the SVC patients of the studied groups. The toxic effects of treatment by the number and degree in patients did not exceed the second degree. Thus, the proposed techniques of high-energy BT in SVC patients are efficient and do not have excessive toxicity.